Fundamentals of entrepreneurship (ENT300) : Creamy cumi ice cream / Faridah Morshidi … [et al.] - Morshidi, Faridah; Mohamad Serpre, Nida Nazihah; Jamail, Nurul Masitah; Raini, Nurul Natasha (2019)
Creamy Cumi Ice Cream offers a lot of Ice Cream flavours for students in UiTM Kota Samarahan Campus 1. This company provide ten ice cream flavours such as Milo, Oreo, Corn, Yam, Matcha Green Tea, Green beans, Chooky-chooky, Bandung and Samboi Our shop is located at Block 1 Kolej Seri Gading and we hired one shop assistant. Our mission is to bring new and unique ice cream flavours for students to try. While our objective is to provide our customers with great services and to satisfy their needs of having good tasting deserts.